Компонентный состав 7S и 11S глобулинов сои у гибридных линий F₆ и их родительских форм - Адамовская, В.Г.; Молодченкова, О.О.; Сичкарь, В.И.; Картузова, Т.В.; Безкровная, Л.Я.; Лаврова, Г.Д. (Фактори експериментальної еволюції організмів, 2015)
Aims. Glycinin (11S globulin) and β-conglycinin (7S globulin) are important seed storage proteins in the soybean. The objective of this work was to study a character of component compositions variation and contents of 11S and 7S globulins in the varieties and F₆ hybrid lines of soybean seed in the connection of food direction soybeen breeding. Methods. 7S and 11S globulins were separated by method, which was developed in the Laboratory of Plant Biochemistry (Patent # 42181). The pictures of 11S and 7S globulins were taken with SDS-PAGE electrophoresis. Results. It was established, that varieties and hybrid lines are characterized by considerable distinctions of 7S and 11S globulins contents and its correlation in the soybeen protein. A connection between 7S and 11S globulins contents and protein contents wasn’t established. The presence of variety polimorphism of the component composition of the 7S and 11S globulins at the F₆ hybrid lines created on the basis of Chinese and Japanese soybeen varieties was shown. Conclusions. The got results open fundamentally new approach of estimation of soybeen seed on a quality of protein and can be used for authetication of soybeen varieties of the food direction.